The Impact of the Corporation on classical Economic Theory - Berle, Adolf A. (Quarterly Journal of Economics, 1965)
Introduction, 25. — Preliminary: Some measurable fact-phenomena, 27; size and scope of large corporate activities, 27; distribution of ownership, 28; change in wealth-holding, 28; source of and power over capital, 29. — I. The shift from “capitalist” control, 30. — II. The immutability of classical economic principles, 31; competition, 32; maximization of profit, 33. — III. Stockholders derive what influence they have from social-political, not from entrepreneurial, factors, 37.